Plasma-enhanced upcycling of mixed plastic waste over La0.6Ca0.4FeO3−δ nano spheres for co-producing hydrogen and high-value carbon - Guoxing Chen; Xiao Yu; Aasir Rashid; Chanchan Li; Marc Widenmeyer; Lina Liu; Bowen Liu; Yi Wang; Gert Homm; Emanuel Ionescu; Tao Shao; Anke Weidenkaff (Results in Engineering)
In this study, we present a novel plasma-enabled method for efficiently decomposing mixed plastic waste into hydrogen and valuable carbon materials. The plasma pyrolysis process exhibited superior performance compared to conventional thermal pyrolysis, achieving an H₂ yield of 24.4 mmol / gplastic, which is >25 times higher than that of the thermal pyrolysis process. The addition of La0.6Ca0.4FeO3−δ nano spheres as a pre-catalyst further enhanced hydrogen yield by 1.8 times while facilitating the production of value-added carbon nanotube composite materials. A life-cycle assessment demonstrated that recycling mixed plastic waste via this method significantly reduces CO₂ emissions compared to conventional thermal pyrolysis. This innovative approach shows great potential and provides a scalable and sustainable solution for managing complex mixed plastic waste, promoting circular economy objectives while enabling industrial applications in clean energy production and advanced material development.